Walt Whitman, passant moderne - Eric Athenot (Anglophonia, 2009)
This article considers the major part played by the city in Leaves of Grass. Starting from an analysis of Whitman’s departure from the Romantic poets’ approach to the urban environment it charts the poems’ progress through various cities and examines the poet’s susceptibility to the language of the working men of Manhattan as the catalyst of his poetic revolution. Elaborating on Baudelaire’s flâneur, the paper finally discusses Whitman’s concept of modernity through an evocation of Manhattan—the city of which the persona of "Song of Myself” proudly calls himself the son—as the idealised territory of a textual democracy in which the reader is made the poet’s equal through an erotics of reading that owes everything to this poetry’s urban origins.